A New Study on Generalized Absolute Matrix Summability - í–zarslan, Hikmet Seyhan (Communications in Mathematics and Applications, 2016)
In this paper, a general theorem on \(| A,p_{n};δ|_{k}\) summability factors, which generalizes a theorem of Bor [4] on \(|\bar{N},p_{n}|_{k}\) summability factors, has been proved by using almost increasing sequences.